Hubungan Cash Flow Terhadap Kapasitas Produksi Pada PT Vista Mitra Surabaya - Darno Darno; Riska Anggraeni (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Prove that there is a relationship between cash flow and production capacity at PT. Vista Partners. The sample used in this study is financial data and production data of PT. Vista Partners. This study uses a quantitative approach with the aim to provide an overview of how PT Vista Mitra manages their cash flow and how it affects the production process. According to the data that I process, cash flow at PT Vista Mitra shows good performance because PT Vista Mitra is able to pay the company's obligations well. Data collection is carried out by the author to obtain information on cash flow processing activities carried out in three ways, namely (a) documentation, (b) observation, and (c) interview. Analysis Techniques used in this study use (a) the classic assumption test, (b) t test, and (c) f test with the help of SPSS software. The hypothesis I use is accepted if significant t is less than α = 0.05. The results of this study prove that production capacity. Payment of Receivables (X₁) has a t value of 1,216 with a significance probability value of 0.236. Significant t is greater than α = 0.05. Means that payment of receivables (X₁) production capacity. Product Sales Results (X₂) has a value of t-0.276 with a significance value of 0.785. Significant α = 0.05. Means that product sales (X₂) have no significant effect on production capacity. Payment of debt (X₃) has a value of t 2,562 with a significance value of 0.017. Significant t is smaller than α = 0.05. This means that debt repayment (X₃) has a production capacity. The cost of raw materials (X₄) has a t value of 1.193 with a significance probability value of 0.244. Significant t is greater than α = 0.05. Means the cost of raw materials (X₄). Labor costs (X₅) has a t value of 1,274 with a significance probability value of 0.215. Significant t is greater than α = 0.05. Means that labor costs (X₅) have no significant effect on production capacity. Other costs (X6) have a value of t 1.091 with a significance probability value of 0.286. Significant t is greater than α = 0.05. Means other costs (X₅) have no significant effect on production capacity.